Challenges of imaging structure and function with MRI. - Turner, R.
Deals with current image reconstruction and processing issues in MRI for the study of tissue structure and function. In image reconstruction, the authors discuss the need for new algorithms that can produce high-resolution images with good signal-to-noise ratio from reduced amounts of data. In image processing, the authors describe outstanding problems in automatic image registration and segmentation
Keywords: MRI; Algorithms; Automatic image registration; Function imaging; High-resolution images; Medical diagnostic imaging; Signal-to-noise ratio; Structure imaging